Chinese Merchants Role of Java Trade in 19th Century - Surya, Riza Afita; Fikriya, Rif'atul (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2021)
Chinese arrival in Java was encouraged with significant factors both internal and external. Chinese in Java eventually brought shifting in economical, social, and political aspect of Java under Dutch realm. In 19th century, Chinese in Java were differed into two clusters, known as peranakan and totok. These two terms possed different languange, culture, economical conditions. This study aimed to determine the role of Chinese merchants of Java during 19th century. The study engaged literature study which includes planning, selection, extraction, and excution. Literature review tries to review several books, scholarly articles, and other relevant sources which focused on particular area. Under Dutch realm, Chinese in Java portrayed many different roles, such as moneylenders, middlemen, kapitan, opium traders, and etec. Chinese were considered active in and around Java as the settled in Netherland Indies trade withi coastal shipping. Chinese possess priviledge spot under Dutch colonial policy, due to their advance skill in business and their independency of local rulers. In term of trade, the Chinese were ubiquitous and essential, since everyone commited trade in Java had to do business with Chinese. Java’s Chinese men and unknown number of peranakan and native Javanese women whom they married or related were almost all participated in the money economy.